FIRE RESISTANCE OF COLD FORMED STEEL FRAMES OF 3D-VOLUMETRIC MODULES IN COMPARISON WITH ROLLED STEEL PROFILES (Collection of scientific works «Modern structures of metal and wood», 2025)
Compared to traditional building materials and techniques, the use of prefabricated modular structures has the potential to solve the problems of environmental impacts such as energy consumption and the associated carbon dioxide emissions. The use of materials with a high potential for recycling and reuse, such as steel in the form of rolled or cold formed profiles, is fully in line with the principles of the circular economy - a shift from a linear to a circular material use. Unlike rolled profiles with open and closed cross-sections made of structural steels, which use intumescent  paints  for  fire  protection,  cold-formed steel  profiles,  due  to  their  relatively  small thickness, require the use of fireproof coatings of greater thickness (10-15 mm) based on gypsum or perlite. For galvanized profiles, the only fire protection method available is cladding using various types of fireboards. The investigation of steel volumetric modules design economic factors influenced by different methods  of  fire  protection  were  conducted  at  the  Department  of  Metal, Wooden  and  Plastic Structures. Further investigation of economical design related factors of fire resistance of cold formed structures of volumetric modular construction intended to fill the gap. The research is focused on the performance of cold formed steel bearing structures, as well as fire resistance of cold formed steel profiles and fire protection methods.
Keywords: cold formed steel; 3D-volumetric modules; fire resistance; steel buildings